A Dual Immunosensor Based on Optical Weak Value Amplification for Simultaneous Detection of CA125 and HE4 - Bei Wang; Gengyu Liang; Lingqin Meng; Han Li; Zishuo Song; Yang Xu; Yonghong He; Deling Duan; Qiuxia Shi; Tian Guan; Ya Gong (Sensors)
Simultaneous detection of multiple biomarkers is essential for effective cancer screening. Taking ovarian cancer as an example, the combined detection of CA125 and HE4 has proven to be the most efficient and accurate among multiple biomarker combinations. In this study, we proposed a dual immunosensor based on weak value amplification (WVA) to detect ovarian cancer. By modifying the sensor surface through a self-assembled monolayer technique and utilizing recombinant protein G for antibody enrichment and directional capture, the sensor enables high-precision, simultaneous detection of CA125 and HE4, with detection limits of 5.39 U/mL and 1.79 ng/mL, respectively. Furthermore, the sensor demonstrates excellent specificity, effectively distinguishing target analytes from non-target molecules. This study provides a novel approach for early cancer screening and clinical diagnosis, highlighting the potential of WVA-based immunosensors in ovarian cancer detection.